RELATIONSHIP BETWEEN EDUCATION AND EXISTING HOUSING CONDITIONS OF ELDERLY PEOPLE - R. UNESHA FAREQ*, T. NEERAJA and V. PRASUNA (The Journal of Research ANGRAU, 2021)
The study aimed to understand the relationship between education andexisting housing conditionsof the elderly. The elderly women in the age group of sixty and above who were able to carry out theirdaily chores were selected as sample. The standard design guidelines evolved through research byvarious Government and Non-government organizations and researchers served as a base to identifythe existing housing conditions of the elderly people.The findings of the study revealed that educationof the respondent was found to be a factor that determined the design of the communication systemsin the home in the residences.Comparatively, highly-educated elderly respondents i.e. who completedgraduation degree or above graduationwere found having technical knowledge and taking theadvantage of technology concerning communication systems in their homes.